Atlee Pine : Long Road to Mercy - Book 1 - Baldacci, David; Brewer, Kyf; Pressley, Brittany (New York, NY : Grand Central Publishing, 2018)
David Baldacci introduces a remarkable new character. Atlee Pine is an FBI special agent assigned to the remote wilds of the western United States. Ever since her twin sister was abducted by a notorious serial killer at age five, Atlee has spent her life hunting down those who hurt others. Now, Atlee is called in to investigate the mutilated carcass of a mule found in the Grand Canyon, and hopefully, solve the disappearance of its rider. But this isn't the only recent disappearance. In fact, it may be just the first clue, the key to unraveling a rash of other similar missing persons cases in the canyon.
Keywords: United States -- Federal Bureau of Investigation -- Fiction -- Officials and employees; Missing persons -- Fiction; Grand Canyon (Ariz.) -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Audiobooks